Long-Term Response of Classic Kaposi's Sarcoma to Intralesional Doxorubicin: A Case Report - Yasir Azim Mirza; Davide Altamura; Torkan Hirbod; Roberto Verdolini (Karger Publishers, 2015)
Classic Kaposi's sarcoma (KS) is a disease with low mortality but high morbidity. The optimum treatment of KS depends upon several factors, including location of lesions, disease progression, severity of symptoms and patient preference. We report the long-term response to the use of intralesional doxorubicin to successfully treat a large cutaneous lesion of KS on a patient refractory to traditional treatments.